Insights into the role of non-coding RNAs in the development of insecticide resistance in insects - Xiao, Huamei; Ma, Chunhui; Peng, Ruizhi; Xie, Meiqiong (Frontiers in Genetics, 2024)
Pest control heavily relies on chemical pesticides has been going on for decades. However, the indiscriminate use of chemical pesticides often results in the development of resistance in pests.Almost all pests have developed some degree of resistance to pesticides. Research showed that the mechanisms of insecticide resistance in insects encompass metabolic resistance, behavioral resistance, penetration resistance and target-site resistance. Research on the these mechanisms has been mainly focused on the cis-regulatory or trans-regulatory for the insecticide resistance-related genes, with less attention paid to non-coding RNAs (ncRNAs), such as microRNA (miRNA), long non-coding RNA (lncRNA), and circular RNA (circRNA). There has been increased studies focus on understanding how these ncRNAs are involved in post-transcriptional regulation of insecticide resistance-related genes. Besides, the formatted endogenous RNA (ceRNA) regulatory networks (lncRNA/circRNA-miRNA-mRNA) has been identified as a key player in governing insect resistance formation. This review delves into the functions and underlying mechanisms of miRNA, lncRNA, and circRNA in regulating insect resistance. ncRNAs orchestrate insect resistance by modulating the expression of detoxification enzyme genes, insecticide target genes, as well as receptor genes, effectively regulating both target-site, metabolic and penetration resistance in insects. It also explores the regulatory mechanisms of ceRNA networks in the development of resistance. By enhancing our understanding of the mechanisms of ncRNAs in insecticide resistance, it will not only provide valuable insights into the new mechanisms of insecticide resistance but also help to enrich new directions in ncRNAs gene regulation research.